Evolución histórica del diseño cavitario - Uribe, Carlos Mario; Gómez, Aurora (Revista Facultad de Odontología Universidad de Antioquia, 2016)
This paper recopilates for teaching purpose a wide review of the literature about the historic evolution of cavity design for the treatment of Dental caries. The must relevant aspect that could be pointed out, is the historic evolution of Operative Dentistry that started with a radical approach to treat caries and has change to a conservative one. In doing so, the development of new: Dental Materials, has new instruments in quantity and quality and the interest of researches and health educators in the intention to help g-roups ancl individuos. This latest content means than Teaching Dentistry should be performed beyond the scope of biotechnics alone.